Discussion: University Governance: Some Omitted Aspects - Barrett, Arnold L. (Academy of Management Journal, 1963)
The article addresses the issue of faculty participation in university governance and the moral and ethical conflicts that can arise as a result. The author reports on the possibility for the administrative role in educational institutions to become equal to the role of scholar-teacher. A discussion is presented about scholarly tasks that could be expected from an employee in administrative positions. Details related to administrative and faculty responsibilities in educational organizations are presented.